2012
DOI: 10.22358/jafs/66082/2012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of particle size of full-fat rapeseed and of multi-carbohydrase enzyme supplementation on nutrient digestibility and performance in broilers

Abstract: The aim of the study was to investigate the effect of the particle size of full-fat rapeseed and of multi-carbohydrase enzyme supplementation on chicken performance. The experiment was conducted with 480 male broiler chickens, divided into four dietary treatments, 15 replications with 8 birds each. Two basal diets were prepared containing fine-ground (FG) or coarse-ground (CG) rapeseed. Diets were unsupplemented or supplemented with a multi-carbohydrase enzyme preparation. The CG rapeseed depressed (P<0.05) bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…These fermentation products were, however, not increased in broilers fed the RSM diets in the present study. Other factors such as the presence of antinutritional factors, glucosinolates, tannins, phytic acid, and sinapine may have resulted in the poor performance of broilers fed the RSM diets (Khajali and Slominski, 2012 ; Rutkowski et al., 2012 ; Ahmed et al., 2014 ). Reduced villus height, deeper crypts, and lower VCR in broilers fed RSM diets compared with those fed the SBM diet may be due to the aforementioned antinutritional factors.…”
Section: Discussionmentioning
confidence: 99%
“…These fermentation products were, however, not increased in broilers fed the RSM diets in the present study. Other factors such as the presence of antinutritional factors, glucosinolates, tannins, phytic acid, and sinapine may have resulted in the poor performance of broilers fed the RSM diets (Khajali and Slominski, 2012 ; Rutkowski et al., 2012 ; Ahmed et al., 2014 ). Reduced villus height, deeper crypts, and lower VCR in broilers fed RSM diets compared with those fed the SBM diet may be due to the aforementioned antinutritional factors.…”
Section: Discussionmentioning
confidence: 99%
“…Adding a multicarbohydrase (xylanase, β-glucanase, hemicellulase, and pectinase) to the diets can promote growth performance in nursery pigs [ 6 , 9 ]. Beyond the efficacy of individual enzymes, the supplementation of multicarbohydrase and phytase complex (MCPC) in diets fed to poultry species have been shown to allow important reductions in energy and nutrients without any adverse effects on the performance of the birds [ 10 , 11 , 12 ]. Meanwhile, as corn, wheat, and soybean are staple food grains for humans, their common application as primary conventional feedstuffs for animals directly competes with their allocation for human consumption, as well as increasing their cost [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Non-starch polysaccharides (NSP), the main components of plant cell walls, and phytate, the main form of plant-derived phosphorus (P), have long been considered the most common antinutritional factors in the major feedstuffs, including corn, soya, wheat, barley, and their by-products [1][2][3][4]. There is growing interest in using enzyme preparations to reduce the antinutritive effects of NSP and phytate, thereby increasing feed efficiency, decreasing nutrient (particularly nitrogen and P) losses via feces and urine, and minimizing the cost of dietary formulation and waste disposal [5][6][7][8][9]. It is documented that phytase can decompose phytate P into inositol and inorganic phosphorus [10,11], while carbohydrases have the potential to enhance the nutritive value of diet by alleviating the physical encapsulation of intracellular nutrients by plant cell walls and thus improving energy and amino acid availability [9].…”
Section: Introductionmentioning
confidence: 99%
“…There is growing interest in using enzyme preparations to reduce the antinutritive effects of NSP and phytate, thereby increasing feed efficiency, decreasing nutrient (particularly nitrogen and P) losses via feces and urine, and minimizing the cost of dietary formulation and waste disposal [5][6][7][8][9]. It is documented that phytase can decompose phytate P into inositol and inorganic phosphorus [10,11], while carbohydrases have the potential to enhance the nutritive value of diet by alleviating the physical encapsulation of intracellular nutrients by plant cell walls and thus improving energy and amino acid availability [9]. Several studies have shown that supplementing a combination of phytase and carbohydrases in corn, wheat or barley-based diets is more beneficial with regard to P digestibility and retention than supplementation of the individual enzymes [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%